Vestibular Endolymphatic Hydrops Visualized by Magnetic Resonance Imaging and Its Correlation With Vestibular Functional Test in Patients With Unilateral Meniere's Disease - Liu, Yupeng; Zhang, Fan; He, Baihui; He, Jingchun; Zhang, Qing; Yang, Jun; Duan, Maoli (Frontiers in Surgery, 2021)
Background: Currently, 3 Tesla-MRI following intratympanic gadolinium injection has made it possible to assess the existence and the severity of hydrops in each compartment of the endolymphatic spaces in vivo. However, the relationship between vestibular endolymphatic hydrops (EH) visualized by MRI and vestibular functional tests, especially the correlation between caloric test, video-head impulse test, and semicircular canal hydrops, has not been well-investigated. Objective: The purpose of this study is to investigate the relationship between the severity of EH in each compartment of otoliths and semicircular canal and the results of vestibular functional tests. Methods: In this retrospective study, we performed three-dimensional fluid-attenuated inversion recovery (3D-FLAIR) sequences following intratympanic gadolinium injection in 69 unilateral patients with definite Menière's disease. Vestibular and lateral semicircular canal hydrops was graded on MRI using a four grade criterion. All patients underwent pure-tone audiometry, cervical vestibular evoked myogenic potential (cVEMP), ocular vestibular evoked myogenic potential (oVEMP), caloric test and video head impulse test (vHIT). The latency, amplitude and asymmetry ratio of VEMP, canal paresis (CP) and vestibulo-ocular reflex (VOR) gain of lateral semicircular canal of vHIT were collected. The correlation analysis were performed between the parameters of function test and EH. Results: Vestibular EH showed correlations with the duration of disease (r = 0.360) and pure tone average (r = 0.326). AR of cVEMP showed correlations with Vestibular EH (r = 0.407). CP (r = 0.367) and VOR gain of lateral semicircular canal at 60 ms (r = 0.311) showed correlations with lateral semicircular canal hydrops. Conclusion: EH in different compartments is readily visualized by using 3D-FLAIR MRI techniques. The degree of vestibular EH correlated with AR of cVEMP and EH in the semicircular canal ampullar affects the caloric and vHIT response in patients with unilateral Meniere‘s disease.